Diverse molecular mechanisms involved in AChR deficiency due to rapsyn mutations. - Cossins, J; Burke, G; Maxwell, S; Spearman, H; Man, S; Kuks, J; Vincent, A; Palace, J; Fuhrer, C; Beeson, D (2006)
Congenital myasthenic syndromes are inherited disorders of neuromuscular transmission characterized by fatigable muscle weakness. Autosomal recessive acetylcholine receptor (AChR) deficiency syndromes, in which levels of this receptor at the neuromuscular junction are severely reduced, may be caused by mutations within genes encoding the AChR or the AChR-clustering protein, rapsyn. Most patients have mutations within the rapsyn coding region and are either homozygous for N88K or heteroallelic for N88K and a second mutation. In some cases the second allele carries a null mutation but in many the mutations are missense, and are located in different functional domains. Little is known about the functional effects of these mutations, but we hypothesize that they would have an effect on AChR clustering by a variety of mechanisms that might correlate with disease severity. Here we expressed RAPSN mutations A25V, N88K, R91L, L361R and K373del in TE671 cells and in rapsyn-/- myotubes to determine their pathogenic mechanisms. The A25Vmutation impaired colocalization of rapsyn with AChR and prevented agrin-induced AChR clusters in rapsyn-/- myotubes. In TE671 cells, R91L reduced the ability of rapsyn to self-associate, and K373del-rapsyn was significantly less stable than wild-type. The effects of mutations L361R and N88K were more subtle: in TE671 cells, in comparison with wild-type rapsyn, L361R-rapsyn showed reduced expression/stability, and both N88K-rapsyn and L361R-rapsyn showed significantly reduced co-localization with AChR. N88K-rapsyn and L361R-rapsyn could effectively mediate agrin-induced AChR clusters, but these were reduced in number and were less stable than with wild-type rapsyn. The disease severity of patients harbouring the compound allelic mutations was greater than that of patients with homozygous rapsyn mutation N88K, suggesting that the second mutant allele may largely determine severity.